2016
DOI: 10.3389/fimmu.2016.00584
|View full text |Cite
|
Sign up to set email alerts
|

Allorecognition of HLA-C Mismatches by CD8+ T Cells in Hematopoietic Stem Cell Transplantation Is a Complex Interplay between Mismatched Peptide-Binding Region Residues, HLA-C Expression, and HLA-DPB1 Disparities

Abstract: HLA-C locus mismatches (MMs) are the most frequent class I disparities in unrelated hematopoietic stem cell transplantation (HSCT) and have a detrimental impact on clinical outcome. Recently, a few retrospective clinical studies have reported some variability in the immunogenicity of HLA-C incompatibilities. To get better insight into presumably permissive HLA-C MMs, we have developed a one-way in vitro mixed lymphocyte reaction (MLR) assay allowing to quantify activated CD56−CD137+CD8+ lymphocytes in HLA-C in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…HLA-C*01 and -*04, highly expressed alleles according to Vince et al ( 9 ), show lower β 2 m/peptide binding stability according to Sibilio et al ( 28 ). Vince et al did not report HLA-C mRNA expression for these alleles, while other studies ( 22 25 ) did not report any particular increase in their mRNA expression. Similarly, HLA-C*01 and -*04 were reported to have a high surface reactivity to MAb DT9 ( 21 ), but since they are also less stably bound to β 2 m/peptide, it is possible that DT9 staining underestimates the real amounts of HLA-C molecules on the cell surface.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…HLA-C*01 and -*04, highly expressed alleles according to Vince et al ( 9 ), show lower β 2 m/peptide binding stability according to Sibilio et al ( 28 ). Vince et al did not report HLA-C mRNA expression for these alleles, while other studies ( 22 25 ) did not report any particular increase in their mRNA expression. Similarly, HLA-C*01 and -*04 were reported to have a high surface reactivity to MAb DT9 ( 21 ), but since they are also less stably bound to β 2 m/peptide, it is possible that DT9 staining underestimates the real amounts of HLA-C molecules on the cell surface.…”
Section: Discussionmentioning
confidence: 88%
“…Adding complexity to this matter, other studies failed to confirm the association between HLA-C expression and these genetic markers ( 22 25 ). Furthermore, a study of a very specific population in Nairobi, Kenya ( 26 ), found that the same HLA-C allotype, HLA-C*07, could be associated with either a low (HLA-C*07:01) or an increased (HLA-C*07:02) rate of seroconversion.…”
Section: Introductionmentioning
confidence: 99%
“…Vigorous T-cell alloresponses can be generated by a high degree of HLA class I mismatching between allogeneic individuals or as little as a single amino acid mismatch (e.g. across HLA-B44 allotypes) 28 , 35 37 . Here we examined whether the closely related alleles HLA-B*57:01 and HLA-B*58:01 are capable of eliciting either anti-HLA-B*58:01 (B*57:01 responder vs B*58:01 stimulator) or anti-HLA-B*57:01 (B*58:01 responder vs B*57:01 stimulator) CD8 + T-cell alloreactivity, which would support distinct presentation of the immunopeptidome.…”
Section: Resultsmentioning
confidence: 99%
“…HLA class I molecules have extremely high allelic polymorphism ( ) ( 13 ), potentially influencing direct alloreactivity in HLA mismatched situations. Indeed, we and others ( 14 16 ) have previously shown that HLA alloantigens can induce variable strengths of alloreactive T-cell response in cellular in vitro assays and in vivo , emphasizing the potential role of the TCR repertoire of the alloreactive responder T-cell population.…”
Section: Introductionmentioning
confidence: 87%
“…One way MLRs were performed as previously described ( 14 , 24 ). Briefly, responder PBMC cells (2x10 6 ) were stimulated at a ratio of 1:1 with 30Gy irradiated stimulator PBMC cells in RPMI 1640 medium (Gibco) supplemented with 10 mM l -glutamine, 100 units/ml penicillin/streptomycin (Gibco) and 10% human AB serum (own preparation).…”
Section: Methodsmentioning
confidence: 99%